The Influence Of Hedonic Shopping Value, And Shopping Lifestyle Against Impulse Buying Behavior Through Product Knowledge - Syukur iman ndraha; Nurafrina Siregar; Mesra (International Journal of Society and Law, 2024)
This study aims to test and analyze hedonic shopping value (X1), shopping lifestyle (X2), and impulse buying behavior (Y) mediated by product knowledge (Z). The sample in this study is consumers with 115 samples taken. The research was conducted from April to June 2024. This study uses quantitative data processed using the SEM-PLS analysis model with Smart PLS 3.0. application. The data source uses primary data taken directly from respondents and secondary data obtained from interviews with customers who come to PT. Jaco Nusantara Mandiri Medan Branch which is located at Store Sun Plaza, Medan Mall, Brastagi Supermarket, Ringroad City Walk Mall, Plaza Medan Fair, and Thamrin Plaza. The results of the study show that hedonic shopping value has a positive and significant influence product knowledge. Shopping lifestyle has a positive and insignificant effect on product knowledge, the product knowledge has a positive and insignificant effect on impulse buying behavior. The hedonic shopping value and shopping life style has a positive and significant effect on product knowledge. Hedonic shopping value and shoppinglifestyle has a positive and significant influence on impulse buying behavior through product knowledge.